PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN DANDAMPAKNYA TERHADAP LOYALITAS PELANGGAN (Studi Pada Pelanggan Warung Makan Ayam Geprek Idola di Semarang) - Dwi Mukzizati, 13.05.51.0059 (Students Journal of Economic and Management, 2017)
The research had an intention to examine the influences of brand image, price perception and the quality of product toward the customerâs satisfaction that affecting the loyalty of using the product. The population of this research are the user of Kartika syrup in Gubug, Grobogan with the total sample of 100 correspondents that has been taken by purposive sampling technique. The research study of this final project proposes seven hypothesis that been tested using linier regression with data processing program spss. Based on that statistical experimentation, I got a result that:brand image has a positive effect and has a significance relation with the satisfaction, price perception has a positive effect and has a significance relation with the satisfaction, and quality of product have a positive effect and significance relation with the satisfaction. The satisfaction it self has a positive impact and significance in loyalty of the customers, the brand image has a positive effect and significance in loyalty of the customers, and price perception has a positive effect and significance in loyalty of the customers. In conclusion, Kartika enterprise ought to raise and keep the brand image, price perception and the quality of product in order to gain the customers loyalty toward Karikaâs products and always giving a satisfaction to the customers.